The Impact of Metacognitive Strategies and Self-Efficacy on Listening Comprehension Among Indonesian High School Students - Hartati, Sri; Nur'Aini, Siti; Sukmaningrum, Rahmawati (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study investigates how metacognitive strategies and self-efficacy beliefs affect listening comprehension in eleventh-grade students, addressing the gap between theoretical recommendations and classroom practice.Method – A quantitative path-analysis design was applied to data from 200 students in Cepu, Central Java, Indonesia. Metacognitive strategy use (planning, monitoring, and evaluating) and self-efficacy beliefs were measured via validated questionnaires; listening comprehension was assessed with a standardized test. Findings – Metacognitive strategies significantly predicted listening comprehension (? = 0.38, R² = 0.41, p < 0.01). Self-efficacy had a stronger direct effect (? = 0.52, R² = 0.56, p < 0.001). Path analysis confirmed partial mediation: self-efficacy accounted for 39% of the strategies’ impact (indirect ? = 0.24, p = 0.003). Together, both constructs explained 63.7% of variance in listening scores (R² = 0.637). Research Implications – These results highlight the importance of integrated instruction that combines explicit metacognitive strategy training with confidence-building interventions. Educators should embed scaffolded strategy lessons and targeted feedback into listening curricula to boost both cognitive skills and learner self-belief.